Teachers’ Practices and Teacher Models: Anísio Teixeira and Initial Teacher Training (Rio de Janeiro, 1932–1935) - Gonçalves Vidal, Diana (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2022)
With the purpose of investigating the relationship between teachers’ practices and teacher models, the present article takes as its main thread the work of Anísio Teixeira at the Teachers School of the Institute of Education, in Rio de Janeiro, between 1932 and 1935. In doing that, it resorts to oral and written sources and dares to outline a research methodology. The narrative is organized into four parts and an introduction. The first part offers a general description of the place where Teixeira’s professional work is developed. Only those aspects of the history of the creation of the Institute of Education deemed as necessary to the study are described. The second part explores the broad features of that teacher practice, interweaving written and oral documentation. In the third part, the focus is on the issue of the sources. As final comments, the importance of historical investigations on teachers’ practice and models is addressed.